An Introduction to Nutrition - Open Textbook Library (Open Textbook Library, 2012)
Welcome to Essentials of Nutrition: A Functional Approach! This book is written for students who are not majoring in nutrition, but want to learn about the fundamental aspects of nutrition and how it applies to their own lives. We have written this book with the assumption that you have little or no prior knowledge of college level chemistry, biology, or physiology. But that does not mean it's not scientific! Nutrition is a science-based discipline, so all the material included is backed up by rigorous scientific research, but it is presented in a clear, easy-to-understand fashion without requiring a background in science.
Chapter 1: Nutrition and You -- Chapter 2: Achieving a Healthy Diet -- Chapter 3: Nutrition and the Human Body -- Chapter 4: Carbohydrates -- Chapter 5: Lipids -- Chapter 6: Proteins -- Chapter 7: Nutrients Important to Fluid and Electrolyte Balance -- Chapter 8: Nutrients Important As Antioxidants -- Chapter 9: Nutrients Important for Bone Health -- Chapter 10: Nutrients Important for Metabolism and Blood Function -- Chapter 11: Energy Balance and Body Weight -- Chapter 12: Nutrition through the Life Cycle: From Pregnancy to the Toddler Years -- Chapter 13: Nutrition through the Life Cycle: From Childhood to the Elderly Years -- Chapter 14: Nutrition and Society: Food Politics and Perspectives -- Chapter 15: Achieving Optimal Health: Wellness and Nutrition -- Chapter 16: Appendix A
In English.
Description based on online resource
Keywords: Biology -- Textbooks